Prototype Lengan Robot Berbasis Arduino Dengan Menggunakan Algoritma Kinematics - Salmon Salmon; Bartolomius Harpad (Jurnal Ilmiah Matrik, 2020)
Robot arms, designed and made by humans with the aim to replace human positions in doing heavy and repetitive work. Besides the robot arm used in the automotive industry, it can also be applied to other manufacturing industries. In designing and processing robotic arms, Kinematics and Arduino algorithms are needed. In making a robot arm we need an algorithm, the Kinematics algorithm, which is one branch of study that studies the geometry of motion, so that sometimes this study is considered a direct branch of mathematics. The results of this research are the Arduino-based Robot Arm Prototype Using Kinematics Algorithm.